Features of formation, confinement and stability of the field reversed configuration - Ryzhkov, S.V. (Вопросы атомной науки и техники, 2002)
The field reversed configuration (FRC) is an innovative confinement system that offers a unique fusion reactor potential because of its compact and simple geometry, transport properties, and high plasma beta. Brief review of the simple compact system with natural advantages and reactor potential is given. Theoretical and experimental results in a FRC plasma study are discussed. Last results in compact toroids research are presented which advance the understanding of the formation and stability properties of the field reversed configuration. Confinement properties of oblate (Elongation<1) and prolate (E>2) FRCs (elliptic shape and racetrack) are discussed. Numerical study is overviewed.